2020
DOI: 10.1017/s1751731119002106
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intravenous arginine infusion on inflammation and metabolic indices of dairy cows in early lactation

Abstract: Enhancing the supply of arginine (Arg), a semi-essential amino acid, has positive effects on immune function in dairy cattle experiencing metabolic stress during early lactation. Our objective was to determine the effects of Arg supplementation on biomarkers of liver damage and inflammation in cows during early lactation. Six Chinese Holstein lactating cows with similar BW (508 ± 14 kg), body condition score (3.0), parity (4.0 ± 0), milk yield (30.6 ± 1.8 kg) and days in milk (20 ± days) were randomly assigne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The use of feed additives is one of the common ways to improve animal production performance. As a typical nutritional feed additive, arginine (Arg) can effectively improve the immune function and production performance of dairy cows ( 12 , 13 ), but it is limited due to its high cost of addition and antagonism reaction with other amino acids. At this time, N -carbamoylglutamate (NCG) can promote the synthesis of endogenous Arg and has become a suitable alternative.…”
Section: Introductionmentioning
confidence: 99%
“…The use of feed additives is one of the common ways to improve animal production performance. As a typical nutritional feed additive, arginine (Arg) can effectively improve the immune function and production performance of dairy cows ( 12 , 13 ), but it is limited due to its high cost of addition and antagonism reaction with other amino acids. At this time, N -carbamoylglutamate (NCG) can promote the synthesis of endogenous Arg and has become a suitable alternative.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, arginine could alleviate the inflammation of excessive immune response [ 17 ]. In porcine intestinal epithelial cells (IPEC-J2), L-arginine obviously suppressed the levels of IL-6, IL-8, IL-1β, and TNF-α induced by LPS, alleviated inflammatory response and maintained intestinal integrity [ 18 ]. However, it is unknown whether arginine can alleviate the inflammation response induced by FAdV-4.…”
Section: Introductionmentioning
confidence: 99%
“…At present, few studies have been conducted to assess quantitative aspects of Arg synthesis and catabolism in the whole body or tissues of ruminants. It is noteworthy, however, that supplementation of Arg via the jugular vein during early lactation alleviated inflammation and metabolic stress in dairy cows [50]. The fact that the abundance of both SLC25A29 and SCL38A9 was greater in skeletal muscle of cows fed RPM suggested that Arg content might have been enriched.…”
Section: Arginine Metabolismmentioning
confidence: 99%